Sustainable Intensification of Feed Value Chains in Mixed Sheep-Barley Systems: Rethinking Waste Management - The Case of Atella. A Baseline Study - Dereje, Eden; Wamatu, Jane; Ekule, Muluken (2024)
In the North Shoa Zone, the primary availability of alcoholic by-products, known locally as ‘Atela’, presents a unique opportunity. Farmers purchase these by-products to feed their livestock. Additionally, some households produce traditional beverages like ‘Areke’ and ‘Tella’, primarily to supplement their animals' diet with ‘Atela’. The emergence of brewery plants in the area further enhances this opportunity, as farmers can utilize brewery by-products, such as spent grain and waste yeast, for livestock feed. Given the abundant production of these by-products in the region, a value chain approach is employed to identify and capitalize on existing opportunities, as well as to determine necessary interventions. This approach aims to enhance competitive advantages by optimizing the entire value chain, rather than focusing on individual segments. The objectives of this study include: